Appeal of e-cigarette flavors: Differences between never and ever use of combustible cigarettes. (1st May 2023) - Tackett, Alayna P.; Dai, Hongying Daisy; Han, Dae-Hee; Vogel, Erin A.; Coreas, Saida I.; Jafarzadeh, Nikki; Gonzalez Anaya, Maria J.; Patel, Devaki; Peraza, Natalia; Mason, Tyler B.; Leventhal, Adam M.
Abstract: Background: Characterizing the appeal of flavored e-cigarette solutions by tobacco product use status can inform regulations to reduce vaping in those who never smoked without discouraging adopting e-cigarettes as a quit-smoking aid. Methods: Adults aged 21+ who currently use tobacco products (N = 119) self-administered standardized puffs of eight non-tobacco flavored and two tobacco-flavored e-cigarette solutions using a pod-style device. Participants rated appeal (0–100 scale) following each administration. Mean differences in flavor appeal ratings were compared between four groups: people who never smoked/currently vape, formerly smoked/currently vape, currently smoke/currently vape, and currently smoke/do not vape (with interest in vaping). Results: The Global Flavor (all non-tobacco vs. tobacco)×Group interaction (p = .028) revealed higher appeal for non-tobacco vs. tobacco flavors in adults who never smoked/currently vape (B[95 %CI] = 13.6[4.1–23.1]), formerly smoked/currently vape (B[95 %CI] = 11.6[4.2–18.9]), and currently smoke/currently vape (B[95 %CI] = 9.3[2.5–11.6]), but not adults who currently smoke/never vaped (B[95 %CI] = −0.1[−5.1 to 4.9]). In flavor-specific analyses, adults who never smoked/currently vape rated strawberry (p = .022), peppermint (p = .028), and menthol (p = .028) more appealing than tobacco flavors. Among adults who formerly smoked/currently vape, strawberry (p < .001), peppermint (p = .009), and vanilla (p = .009), were more appealing than tobacco. Adults who currently smoked/currently vape rated peppermint (p = .022) and vanilla (p = .009) as more appealing than tobacco. No non-tobacco flavors were more appealing than tobacco in adults who currently smoke/never vaped. Conclusions: E-cigarette sales restrictions on non-tobacco flavors, including menthol, may eliminate products preferred by adults who vape, including those who never smoked, without discouraging adults who currently smoke and never vaped from trying e-cigarettes. Highlights: No non-tobacco flavors were more appealing than tobacco in adults who currently smoke/never vaped. For people who formerly smoked/currently vape, strawberry, peppermint, and vanilla were more appealing compared to tobacco. Menthol substantially improved appeal for people who never smoked/currently vape but not for the other tobacco use statuses.